Governing the Climate-Energy Nexus Institutional Complexity and Its Challenges to Effectiveness and Legitimacy - Zelli, Fariborz; Bäckstrand, Karin; Nasiritousi, Naghmeh; Skovgaard, Jakob; Widerberg, Oscar (Physical Sciences, 2020)
Analysing the interactions between institutions in the climate change and energy nexus, including the consequences for their legitimacy and effectiveness. Prominent researchers from political science and international relations compare three policy domains: renewable energy, fossil fuel subsidy reform, and carbon pricing. This title is also available as Open Access on Cambridge Core.